Competition and Risk Aversion - Reichenberger, Amanda (Kansas State University. K-State Libraries, 2017)
This study tested the influence of competition and risk aversion on risk-involved investment decisions. The primary base for research lay within message framing and prospect theory. Participants took 1 of 4 different versions of a survey with only the message frame of the manipulated paragraph varying by risk (high or low) and outcome (high competition or low competition. Participants were Kansas State University affiliated students gathered by convenience sampling. Contrary with predictions, testing of the participants’ surveys revealed no significant difference in investment amounts based on the interaction of risk-framing and outcome-framing However, a significant difference in investment amounts was apparent based on risk-framing.
Citation: Reichenberger, A. (2017). Competition and Risk Aversion. Unpublished manuscript, Kansas State University, Manhattan, KS.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, honorable mention
Keywords: Risk aversion; Decision making; Investments; Risk framing; Outcome framing; Prospect theory